2014
DOI: 10.1371/journal.pone.0092448
|View full text |Cite
|
Sign up to set email alerts
|

Current European Labyrinthula zosterae Are Not Virulent and Modulate Seagrass (Zostera marina) Defense Gene Expression

Abstract: Pro- and eukaryotic microbes associated with multi-cellular organisms are receiving increasing attention as a driving factor in ecosystems. Endophytes in plants can change host performance by altering nutrient uptake, secondary metabolite production or defense mechanisms. Recent studies detected widespread prevalence of Labyrinthula zosterae in European Zostera marina meadows, a protist that allegedly caused a massive amphi-Atlantic seagrass die-off event in the 1930's, while showing only limited virulence tod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 67 publications
1
31
1
Order By: Relevance
“…This could be due to any number of factors (e.g., differing plant genetics or condition within and among experiments, or changing pathogen condition over time). However, this species can be present in both green and lesioned leaves, and may modulate host immunity (Brakel et al 2014). Additionally, our cross-host infection experiments indicate at least the possibility for some Labyrinthula, such as our isolate 8b (haplotype 8, species E), to become novel pathogens (e.g., in Z. marina or P. oceanica beds), though 8b's reduced virulence on species like Z. marina (this study) might equally argue against it causing epidemics as such an invasive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to any number of factors (e.g., differing plant genetics or condition within and among experiments, or changing pathogen condition over time). However, this species can be present in both green and lesioned leaves, and may modulate host immunity (Brakel et al 2014). Additionally, our cross-host infection experiments indicate at least the possibility for some Labyrinthula, such as our isolate 8b (haplotype 8, species E), to become novel pathogens (e.g., in Z. marina or P. oceanica beds), though 8b's reduced virulence on species like Z. marina (this study) might equally argue against it causing epidemics as such an invasive.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies nor the study that provided the original 18S rDNA identification of L. zosterae (Leander and Porter 2001) paired sequencing directly with pathogenicity testing for their isolates. However, Brakel et al (2014) did pair geographically based isolate assays and sequencing, but specifically for L. zosterae and only within European eelgrass beds. Thus, at the time of this analysis, the only studies to couple broader assays (across-host-species and large geographic ranges) of isolate pathogenicity with molecular identification are from terrestrial systems, which suggest a hidden diversity of pathogenic and non-pathogenic Labyrinthula for Poaceae hosts (Craven et al 2005;Douhan et al 2009).…”
Section: Communicated By Kenneth Duntonmentioning
confidence: 99%
“…Although L. zosterae has been shown to be able to cause wasting disease symptoms [58], not all species from the Labyrinthula genus are pathogenic [59]. Indeed, recent work has shown that current isolates from European Z. marina populations display varying virulence [60,61], and Labyrinthula spp. seem to be very common in northern Z. marina beds [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although macroalgae and seagrasses form habitats worldwide known as hotspots of biodiversity and production, we know little about the microbes in these ecosystems (Bengtsson et al, 2012), but see Clasen and Shurin (2015) for an ecosystem approach. The relative few microbial studies performed have focused almost exclusively on (epi-)bacterial communities associated to seagrasses and macroalgae, neglecting most other microbes (Bengtsson et al, 2012;Bockelmann et al, 2012Bockelmann et al, , 2013Michelou et al, 2013;Brakel et al, 2014Brakel et al, , 2017Cúcio et al, 2016;Singh and Reddy, 2016). On top of that, particularly functional interactions between marine macrophytes and their microbiomes are poorly known.…”
Section: A3 Marine Macrophyte Holobionts and Their Hologenomesmentioning
confidence: 99%